Current thinking in the health care management of children with cerebral palsy. Issue 3 (10th February 2019) - Graham, David; Paget, Simon P; Wimalasundera, Neil
Summary: Cerebral palsy is a developmental disorder of movement and posture which is often associated with comorbidities. While there is currently a limited range of evidence‐based treatments that change the underlying pathology of cerebral palsy, there are many areas in which health care professionals can change the natural history of cerebral palsy and improve participation and quality of life for children with this condition. Early identification has become of paramount importance in the management of cerebral palsy, and it is hoped that it will allow earlier access to cerebral palsy interventions that may improve the natural history of the condition. Common challenges in the management of cerebral palsy include spasticity and dystonia, management of pain, hip surveillance, sleep and feeding, swallowing and nutrition. The six Fs framework (function, family, fitness, fun, friends and future) provides a guide to developing shared goals with families in the management of cerebral palsy.